2018
DOI: 10.1155/2018/2325659
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Phytochemical Composition, and Enzyme Inhibitory Activities of Some Indigenous Weed Plant Extracts in Fruit Fly, Drosophila melanogaster

Abstract: Drosophila melanogaster being used as model organism is considered as pest of homes, restaurants, and fruit markets. The damaged fruits are also reported to serve as a carrier for various diseases. The current study was designed to evaluate the toxicity of petroleum extract of some weed plants, namely, Euphorbia prostrata, Parthenium hysterophorus, Fumaria indica, Chenopodium murale, and Azadirachta indica, against D. melanogaster. Mortality at 10, 20, and 30% concentrations after 24 and 48 hours was found com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
(43 reference statements)
1
26
0
3
Order By: Relevance
“…Result of the survival assay showed that flies exposed to APN (0-100 mg/mL) caused 100 % mortality at 50 mg/mL and 100 mg/mL. 24,44 Finding from the study also showed that there was a significant increase (p < 0.05) in the concentration of malondialdehyde (MDA) at 32 mg/mL of APN when compared to the control. MDA is an important biomarker for accessing the level of lipid peroxidation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Result of the survival assay showed that flies exposed to APN (0-100 mg/mL) caused 100 % mortality at 50 mg/mL and 100 mg/mL. 24,44 Finding from the study also showed that there was a significant increase (p < 0.05) in the concentration of malondialdehyde (MDA) at 32 mg/mL of APN when compared to the control. MDA is an important biomarker for accessing the level of lipid peroxidation.…”
Section: Resultsmentioning
confidence: 93%
“…Locomotive performance of flies treated on different concentration of APN was examined using negative geotaxis assay described previously. 24 After seven days exposure to APN, 10 APN treated flies were made inactive under light anaesthesia on ice and transferred to a vertical column that is labelled and has a length and diameter of 15 and 1.5 cm respectively. All the columns were marked before that time at a 6 cm point.…”
Section: Negative Geotaxis Assaymentioning
confidence: 99%
“…Furthermore, the bioactive compound has a potency for inhibition of larvae growth through direct contact. The previous study proved that the phytochemical content, especially tannin and phenol, also had a potency as a larvicidal agent (Riaz et al, 2018), the poisonous contact to the larvae body will cause morphological abnormalities on the larvae body (Bosly, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Several medicinal plants such as Momordica charantia and Andrographis paniculata have been reported in inhibiting the replication cycle of DENV. Few of the weed plants have been shown to cause insecticidal and enzyme inhibitory activities in insects [83,84]. Further investigations are needed to develop potential dengue treatment [85].…”
Section: Botanical Controlmentioning
confidence: 99%